Preparation and application of Taq DNA polymerase monoclonal antibody guided by structural domain analysis - Xiaoqian Zhu; Tingting Zhang; Haiyu Zhao; Bingbing Hou; Mingyue Fu; Qianshan Zhao; Tong Xu; Jixiang Zhao; Jiming Xie; Yuyao Zhou; Suxia Li; Peng Wang (PLoS ONE, 2026)
Hot-start polymerase chain reaction (hot-start PCR) effectively inhibits non-specific product amplification during PCR, with hot-start Taq DNA polymerase (HS Taq) serving as the critical component. Current HS Taq preparation methods, including chemical modification and aptamer-based approaches, exhibit limitations such as prolonged activation time, reduced enzyme activity, and inadequate blocking specificity. In contrast, antibody-mediated hot-start Taq offers distinct advantages: rapid activation, stable enzymatic performance, and high blocking specificity through targeted binding to functional domains. While antibody-based hot-start Taq DNA polymerases are widely utilized for their high efficiency and specificity, their development often relies on commercial sources or complex genetic engineering. This dependency constrains the independent and customizable development of core PCR components. To address this, our study established a streamlined platform for generating highly effective monoclonal antibodies that inhibit Taq enzyme activity. The key innovation lies in our structure-guided, domain-specific immunization strategy: instead of using the full-length enzyme, we targeted the polymerase domain (Taq-P) to generate a specific monoclonal antibody that acts as a reversible inhibitor. This approach overcomes the major challenge of generating functional antibodies against cryptic epitopes, which are poorly immunogenic in the full-length protein. This antibody sterically blocks the enzyme’s active site at room temperature, preventing non-specific priming during PCR setup, and dissociates upon thermal activation to restore full activity. The resulting hot-start Taq enzyme significantly reduced non-specific amplification in quantitative PCR assays, and its practical utility was successfully demonstrated in detecting fungal pathogens and respiratory viruses using clinical samples. This study provides a feasible and effective strategy for the autonomous development of critical reagents for molecular diagnostics.